Сontent of interleukin TNF - α, IL-2 and IL-10 in blood in the time of secondary-chronic inflammation during treatment with glyukozaminilmuramildipeptid - Shevchenko, O. M.; Bibichenko, V. O. (Journal of Education, Health and Sport, 2017)
Shevchenko O. M., Bibichenko V. O. Содержание интерлейкинов ФНО - α , ИЛ-2 и ИЛ-10 в крови при вторично-хроническом воспалении на фоне применения глюкозаминилмурамилдипептида = Сontent of interleukin TNF - α, IL-2 and IL-10 in blood in the time of secondary-chronic inflammation during treatment with glyukozaminilmuramildipeptid = Вміст інтерлейкінів ФНО - α, ІЛ-2 та ІЛ-10 у крові при вторинно хронічному запаленні на тлі застосування глюкозамінілмурамілдипептиду. Journal of Education, Health and Sport. 2016;6(11):685-701. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221666 http://ojs.ukw.edu.pl/index.php/johs/article/view/4114 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. УДК 616-002,2-085.37-092-078:57.083.3 Содержание интерлейкинов ФНО - α , ИЛ-2 и ИЛ-10 в крови при вторично-хроническом воспалении на фоне применения глюкозаминилмурамилдипептида А. Н. Шевченко, В. А. Бибиченко Харьковский национальный медицинскиий университет, г. Харьков, Украина Реферат В эксперименте на крысах показано, что при воспалении на фоне применения глюкозаминилмурамилдипептида по сравнению с естественным течением снижается концентрация провоспалительных цитокинов ФНО – α и ИЛ - 2, значительно снижается концентрация противовоспалительного цитокина ИЛ-10. Следовательно, использование глюкозаминилму-рамилдипептида приводит к снижению хронизации воспаления. Ключевые слова: вторично хроническое воспаление, периферическая кровь, цитокины, глюкозаминилмурамилдипептид. content of interleukin TNF - α, IL-2 and IL-10 in blood in the time of secondary-chronic inflammation during treatment with glyukozaminilmuramildipeptid O. M. Shevchenko, V. O. Bibichenko Kharkiv National Medical University, Kharkov, Ukraine Abstract In an experiment on rats was showed that concentration of proinflammatory cytokines TNF - α and IL - 2 reduced and concentration of anti-inflammatory cytokine IL-10 significantly reduced in the time of secondary-chronic inflammation during treatment with glyukozaminilmuramildipeptid compared to the natural course of inflammation. Consequently, the treatment with glyukozaminilmuramildipeptid reduces chronic inflammation. Keywords: secondary chronic inflammation, peripheral blood, cytokines, glyukozaminilmuramildipeptid. Вміст інтерлейкінів ФНО - α, ІЛ-2 та ІЛ-10 у крові при вторинно хронічному запаленні на тлі застосування глюкозамінілмурамілдипептиду О. М. Шевченко, В. О. Бібіченко Харківський національний медичний університет, м. Харків, Україна Реферат В експерименті на щурах показано, що при запаленні на тлі застосування глюкозамінілмурамілдипептиду в порівнянні з природним перебігом знижується концентрація прозапальних цитокінів ФНО - α і ІЛ - 2, значно знижується концентрація протизапального цитокіну ІЛ-10. Отже, використання глюкозамінілмурамілдипептиду призводить до зниження хронізації запалення. Ключові слова: вторинно хронічне запалення, периферична кров, цитокіни, глюкозамінілмурамілдипептид.